2022
DOI: 10.36841/pioneer.v14i1.1274
|View full text |Cite
|
Sign up to set email alerts
|

Metaphors and Similes in Peter Lerangis' Novel The Curse of the King

Abstract: This study aims to reveal the writing style in the novel The Curse of the King by Peter Lerangis, especially in its figurative speech namely metaphor and simile. The classification of metaphors analyzed uses Newmark's classification and the simile classification used in this study is the classification described by Fromilhague. A qualitative method was used to answer the problem of the study. The research showed that there were thirteen metaphors and fifty-two similes. The metaphor compositions found were one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The words and phrases from the novel that were selected and created as a component of qualitative data-collection process for this study in order to evaluate or comprehend phenomena serve as the study's primary source of information (Flick, 2018). Finding sentences and phrases that match the formulation of the problem is the intention of the data collection strategy used in this study (Bowo et al, 2022). In this case, we looked for the data containing similes that normally use the linking words "like" or "as" in phrases and sentences.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The words and phrases from the novel that were selected and created as a component of qualitative data-collection process for this study in order to evaluate or comprehend phenomena serve as the study's primary source of information (Flick, 2018). Finding sentences and phrases that match the formulation of the problem is the intention of the data collection strategy used in this study (Bowo et al, 2022). In this case, we looked for the data containing similes that normally use the linking words "like" or "as" in phrases and sentences.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, a number of studies' findings indicate that implicit similes are more frequently discovered than explicit similes in their chosen novel studies. For instance, in their analysis of metaphors and similes in Peter Lerangis' novel, The Curse of the King, Bowo et al (2022) discovered 47 implicit similes and only 5 explicit similes. Similarly, in a case study of "Animal Farm" by Fadaee (2010), the study of symbols, metaphors, and similes in the literature revealed that the author used implicit similes more frequently than explicit similes (84.85% versus 15.15%, respectively).…”
Section: Implicit Similes Examples In the Novelmentioning
confidence: 99%
See 1 more Smart Citation